Community Preference on Scenario Management of Baturraden Botanical Garden in Central Java - Herawikan Mandiriati; Djoko Marsono; Erny Poedjirahajoe; Ronggo Sadono (Foresty Faculty of Hasanuddin University, 2018)
Botanical garden as a preservation area has an important role supporting the plant conservation efforts. It is the best source of information to study about plant distribution and its habitat attributes. Botanical garden can also provide environmental education for the community. Indonesia has a big number of botanical gardens, one of them is Baturraden Botanical Garden, located in Central Java. It is the largest botanical garden in Java Island with its area reaches 143.5 hectares. Currently, Baturraden Botanical Garden management has a serious problem about the high dependence of community in its area. Therefore, it is important to formulate the scenario management that can integrate between the community desires and its direction management. This study aimed to identify the community preference on scenario management of Baturraden Botanical Garden. Data collection was conducted by the questionnaire method using accidental sampling technique. The number of respondents was about 109 people older than 15 years old. This criterion was decided with the assumption that the respondent who had the range of age, having good knowledge about the function of Baturraden Botanical Garden as preservation area. Data analysis was done using Analytical Hirarycal Process. This method was selected because it was capable to describe the normative preference by the number. The result showed that the community preference on scenario management of Baturraden Botanical Garden based on the scale of priority is ecotourism development (0.269); optimization of water resource (0.232); intensification of plant conservation (0.197); environmental education (0.189); and intensive research (0.175).